Life on the Autism Spectrum - Burge, Garry (IJRDO - Journal of Social Science and Humanities Research, 2016)
Being Autistic can be very challenging, for even though you look the same as other people, they unfortunately do not understand the different way you think and function. For instance, I often think outside the box, but sadly in a society like Australia, „outside the box‟ thinking is something that is not harnessed. I managed to self-publish my own book titled “I Want To Work An Asperger Story”. This book provides an account of my own challenges and life growing up as someone on the Autism Spectrum and furthermore contains a Foreword from Doctor Tony Attwood. It is very hard to publish and distribute books in Australia as people seem more interested in both sport and drinking alcohol for pointless reasons. So to get the book both published and distributed was in itself a challenge. The book however is in some libraries, as well as the library I currently work in as a Service Support Assistant within the Social Sciences & Humanities Library at the University of Queensland here in Brisbane, Australia.